2019
DOI: 10.32404/rean.v6i2.2658
|View full text |Cite
|
Sign up to set email alerts
|

Heterose Em Híbridos De Melancia

Abstract: A melancia é uma curcubitácea bastante difundida no mundo, predominando nos cultivos comerciais o uso de híbridos. Apesar desse cenário, poucos são os trabalhos que relatam a magnitude e efeito da heterose em caracteres de interesse nesta cultura. O objetivo desse trabalho foi estimar a heterose em híbridos de melancia para características agronômicas e qualidade dos frutos. Os tratamentos foram constituídos de 22 genótipos, sendo 15 híbridos experimentais obtidos do cruzamento de seis genitores: quatro cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Isso significa que, com o aumento das dosagens de nitrogênio, aumenta-se também a relação polpa/casca. Apesar de ser uma característica desejada, o afinamento em excesso da casca pode prejudicar a resistência do fruto ao transporte, do manejo ao acondicionamento, haja vista que, entre os cultivares utilizados no Brasil, aqueles de frutos com casca mais espessa são mais adequados ao tipo de transporte predominante no mercado interno (Tavares et al 2019).…”
Section: Fonte: Autores (2022)unclassified
“…Isso significa que, com o aumento das dosagens de nitrogênio, aumenta-se também a relação polpa/casca. Apesar de ser uma característica desejada, o afinamento em excesso da casca pode prejudicar a resistência do fruto ao transporte, do manejo ao acondicionamento, haja vista que, entre os cultivares utilizados no Brasil, aqueles de frutos com casca mais espessa são mais adequados ao tipo de transporte predominante no mercado interno (Tavares et al 2019).…”
Section: Fonte: Autores (2022)unclassified
“…In the United States, in addition to the icebox type, commercial watermelon fruits are, in general, classified into four categories: small (5.5-8.0 kg), medium (8.1-11.0 kg), large (11,1-14.5 kg) and extra-large (greater than 14.5 kg) [9]. Martins et al (2013) [25] reported average fruit weight around 3.7 kg under uses of biostimulants in the 'Quetzali' and 'Style' hybrids whereas Tavares et al (2019) [3] investigated the effect of heterosis in 15 watermelon hybrids and reported average fruit weight ranging from 6 to 10 kg, both results outstanding 2-4fold than all of our studied hybrids. In the Brazilian market, it still prevails the appreciation for fruits with weight above 6 kg, Crimson Sweet standard [25].…”
Section: Hybrids Physical Characteristics Fw (G) Ld (Cm) Td (Cm) Fsi St (Cm) F (N)mentioning
confidence: 99%
“…The soluble solids are a valuable measurement due to the higher total soluble solids content being associated with the greater commercial performance of the selected hybrid [3]. It is also noteworthy that soluble solids are very influenced by environmental factors, among which stand out the genotype, planting location and crop management [31].…”
Section: Hybrids Physical Characteristics Fw (G) Ld (Cm) Td (Cm) Fsi St (Cm) F (N)mentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology of Gardner and Eberhart (1966) for diallel crosses is one of the most preferred for allogamous plants because it allows for a detailed examination of the components of heterosis (NASCIMENTO et al, 2010;TAVARES et al, 2019) and of the types of effects involved in controlling the trait(s) of interest.…”
Section: Introductionmentioning
confidence: 99%